2021
DOI: 10.1002/jso.26467
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term oncological outcomes of the sphincter preserving total mesorectal excision with varying distal resection margins

Abstract: Introduction: A subcentimeter distal resection margin (DRM) appears to be acceptable for most patients, however, long-term follow up and specific subsets where DRM would influence recurrences have not been adequately investigated. Methods: A retrospective analysis of all sphincter-preserving resections for mid and low rectal cancers between July 2011 and May 2015 was performed. Extended total mesorectal excisions (TME) and patients with positive pathologic circumferential margins (CRM) were excluded. Results: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Other reports have recently analyzed the role of the DRM in patients with rectal cancer 18 . They demonstrated that the DRM did not influence oncologic outcomes, except in patients who had a poor response to neoadjuvant radiation.…”
Section: Discussionmentioning
confidence: 99%
“…Other reports have recently analyzed the role of the DRM in patients with rectal cancer 18 . They demonstrated that the DRM did not influence oncologic outcomes, except in patients who had a poor response to neoadjuvant radiation.…”
Section: Discussionmentioning
confidence: 99%
“…Advancements in surgical technique, precise instrumentation and the use of surgical staplers have increased the rate of sphincter preservation without detriment in the long-term oncological outcomes. 1,2 Continence is attributed to several factors: the anal sphincter complex (anatomical) and the rectum with its reservoir and neurological functions (physiological). Surgical treatment changes the structure and the physiology of the anorectum, leading to functional problems.…”
Section: Introductionmentioning
confidence: 99%
“…Continence is perhaps the most critical issue in treated rectal cancers from a patient's perspective and functional outcomes. Advancements in surgical technique, precise instrumentation and the use of surgical staplers have increased the rate of sphincter preservation without detriment in the long‐term oncological outcomes 1,2 . Continence is attributed to several factors: the anal sphincter complex (anatomical) and the rectum with its reservoir and neurological functions (physiological).…”
Section: Introductionmentioning
confidence: 99%
“…While there was once considered a 5-cm rule for the distal margin in rectal cancer, the safe distal resection margin has been reduced to 1 cm or less in low rectal tumors with the emergence of neoadjuvant multimodal therapy and tumor downstaging. 1 2 The reduction in distal resection margin has increased the boundaries for sphincter preservation in patients with tumors that were once determined to require an abdominoperineal resection (APR). With an increase in patients who could have sphincter preservation, there is a need to describe technique and options for restoration of intestinal continuity with a colon to anal anastomosis.…”
mentioning
confidence: 99%